Multiple Objective Fractional Subset Programming Based on Generalized (ρ, η, A)-Invex Functions - Verma, Ram U. (Journal of Informatics and Mathematical Sciences, 2011)
Motivated by the recent investigations [7,8,10,11,12], a general framework for a class of (ρ, η, A)-invex n-set functions is introduced, and then some results on the optimality conditions for multiple objective fractional subset programming on the generalized (ρ, η, A)-invexity are explored. The obtained results are general in nature and seem to be application-oriented to other results on fractional subset programming in literature.